Randomized placebo-controlled trial comparing efficacy of nonablative fractional photothermolysis combined with topical calcipotriol for the treatment of keloid and hypertrophic scar - Pongprutthipan, Marisa; Rojarayanont, Nattaporn (Chulalongkorn Medical Journal, 2023)
Background : Nonablative fractional laser resurfacing has been shown to have size reduction effect on hypertrophic scar with minimal side effects; and antifibrotic effect of vitamin D in keloid fibroblasts has been reported in vitro. A combination of the two treatments should gain additional benefits from facilitation of wound healing, transdermal drug delivery and recurrence prevention. Objectives : To evaluate the efficacy of nonablative fractional laser resurfacing combined with topical calcipotriol for the treatment of keloid and hypertrophic scar. Methods : Subjects were treated with six fractional 1,550 nm Ytterbium/Erbium: fiber laser treatment weekly for entire lesion. Each lesion was randomly treated with topical calcipotriol or white petrolatum twice daily. Follow-up visits were done at week 6th and 12th. Clinical appraisal achieved by Patient and Observer Scar Assessment Scale (POSAS) and evaluator blinded photographic clinical assessment. Results : Twelve subjects completed treatments in the study. Mean POSAS showed significant reduction (P <0.05) at week 6 but no statistical difference between groups was observed. Photographic clinical assessment had mild (1 - 25%) to moderate (26 - 50%) improvement in majority of the cases but there was no statistical difference between groups. Conclusion : Nonablative fractional laser is an effective treatment for keloids and hypertrophic scars while the benefit of topical calcipotriol could not be demonstrated in the study.